The Personalities and Inner Conflicts of Teachers in Three Modern Indonesian Novels Reviewed from a Literary Psychology Perspective - Ambarsari, Zukhruf; Lubis, Malan; Ritonga, Mara Untung (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The thesis aims to analyze the teachers' personalities and inner conflicts in three modern Indonesian novels because the writer sees many inner conflicts experienced by the teachers through the characters in the novel. A qualitative approach was conducted in this study. The psychology approach is used to analyze literature exhaustively, the extrinsic and intrinsic sides. The data analysis can be concluded that there are three Modern Indonesian novels such as; Guru Aini by Andrea Hirata, Kembara Rindu by Habiburrahman El Shirazy, and Si Anak Special by Tere Liye. The technique of analyzing the data of this study was applied by observation, interview, and questionnaire. The writer analyzes qualitative data interactively and continues until finished and the data has saturated, starting with data reduction, data display, and conclusion drawing/verification. The validity of this research used theoretical triangulation. The study results showed that the teacher's personality was expressed in three modern Indonesian novels based on academic psychology, namely the personality of high commitment, enthusiasm for work, sincerity in work, high ambition, patience, and firm convictions. The teacher's inner conflict in three Modern Indonesian novels based on a review of academic psychology is the inner approach-avoidance conflict and avoidance conflict, and approach - approach conflict.